Drosophila melanogaster as a tractable eco-environmental model to unravel the toxicity of micro- and nanoplastics. - W?ng, Y.; Jiang, Y. (Environment International, 2024)
Micro- and nanoplastics have emerged as pervasive environmental pollutants with potential ecotoxicological impacts on various organisms, including the model organismDrosophila melanogaster. Here we comprehensively synthesize current research on the adverse effects of micro- and nanoplastics onDrosophila, highlighting key findings and identifying gaps in the literature. Micro- and nanoplastics can lead to physical damage, oxidative stress, inflammation, genotoxicity, epigenetic changes, apoptosis, and necrosis inDrosophila. Exposure to plastic debris affects nutrient absorption, energy metabolism, and reproductive health, often in a sex-specific manner. For instance, male flies are generally more susceptible to the toxic effects of polystyrene microplastics than female flies, showing greater mortality and metabolic disruptions. Furthermore, the combined exposure of plastics with heavy metals can exacerbate toxic effects, leading to enhanced oxidative stress, genotoxicity, and gut damage. While antagonistic effects have been identified particularly with silver compounds, where polystyrene microplastics reduce the bioavailability and toxicity of silver. The adverse effects of plastic particles onDrosophiladepend on size, with smaller particles penetrating deeper into tissues and eliciting stronger toxic responses. The chemical composition of the plastics and the presence of additives also play crucial roles in determining toxicity levels. Chronic exposure to low levels can be as harmful as acute high-dose exposure, highlighting the need for comprehensive, long-term studies to fully understand the ecological and biological impacts of plastic pollution.